2023
DOI: 10.1101/2023.09.18.557956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective refueling of CAR T cells using ADA1 and CD26 boosts antitumor immunity

Yue Hu,
Abhijit Sarkar,
Kevin Song
et al.

Abstract: CAR T cell therapy has revolutionized the treatment of hematologic malignancies, but its efficacy in solid tumors remains limited due to the immunosuppressive nature of the tumor microenvironment and the inability of T cells to persist and traffic to the tumor site. While current strategies focus on enhancing CAR T cell activity through costimulatory molecules and cytokines, a critical yet often overlooked factor is the competition for nutrients between tumor cells and T cells in the nutrient-deprived tumor mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…However, in the tumor microenvironment, TGF‐β‐1 inhibits the expression of CD26, thereby reducing T cell activity. Consequently, in CAR‐T therapy for malignant hematological tumors, increased levels of TGF‐β may weaken the effector function of CAR‐T cells 69 . Studies have shown that knocking out the endogenous TGF‐β receptor II (TGFBR2) in CAR T cells using CRISPR/Cas9 technology can reduce the induction of Treg transformation and prevent exhaustion of CAR T cells 70 .…”
Section: Tumor Microenvironment and Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the tumor microenvironment, TGF‐β‐1 inhibits the expression of CD26, thereby reducing T cell activity. Consequently, in CAR‐T therapy for malignant hematological tumors, increased levels of TGF‐β may weaken the effector function of CAR‐T cells 69 . Studies have shown that knocking out the endogenous TGF‐β receptor II (TGFBR2) in CAR T cells using CRISPR/Cas9 technology can reduce the induction of Treg transformation and prevent exhaustion of CAR T cells 70 .…”
Section: Tumor Microenvironment and Immune Functionmentioning
confidence: 99%
“…Consequently, in CAR-T therapy for malignant hematological tumors, increased levels of TGF-β may weaken the effector function of CAR-T cells. 69 Studies have shown that knocking out the endogenous TGF-β receptor II (TGFBR2) in CAR T cells using CRISPR/Cas9 technology can reduce the induction of Treg transformation and prevent exhaustion of CAR T cells. 70 Thus, the increase of TGF-β in the tumor microenvironment during CAR-T therapy may diminish the cytotoxic effects of CAR-T cells, limiting their ability to recognize and eliminate tumor cells, thereby affecting treatment outcomes.…”
Section: Cytokinesmentioning
confidence: 99%